Secondary Open Aortic Procedure Following Thoracic Endovascular Aortic Repair: Meta‐Analytic State of the Art. Issue 9 (13th September 2017) - Gambardella, Ivancarmine; Antoniou, George A.; Torella, Francesco; Spadaccio, Cristiano; Oo, Aung Y.; Gaudino, Mario; Nappi, Francesco; Shaw, Matthew A.; Girardi, Leonard N.
Abstract : Background: Thoracic endovascular aortic repair is characterized by a substantial need for reintervention. Secondary open aortic procedure becomes necessary when further endoluminal options are exhausted. This synopsis and quantitative analysis of available evidence aims to overcome the limitations of institutional cohort reports on secondary open aortic procedure. Methods and Results: Electronic databases were searched from 1994 to the present date with a prospectively registered protocol. Pooled quantification of pre/intraoperative variables, and proportional meta‐analysis with random effect model of early and midterm outcomes were performed. Subgroup analysis was conducted for patients who had early mortality. Fifteen studies were elected for final analysis, encompassing 330 patients. The following values are expressed as "pooled mean, 95% confidence interval." Type B dissection was the most common pathology at index thoracic endovascular aortic repair (51.2%, 44.4–57.9). The most frequent indication for secondary open aortic procedure was endoleak (39.7%, 34.6–45.1). More than half of patients had surgery on the descending aorta (51.2%, 45.8–56.6), and one fourth on the arch (25.2%, 20.8–30.1). Operative mortality was 10.6% (7.4–14.9). Neurological morbidity was substantial between stroke (5.1%, 2.8–9.1) and paraplegia (8.3%, 5.2–13.1). At 2‐year follow‐up, mortality (20.4%, 11.5–33.5) and aortic adverse event (aortic death 7.7%, 4.3–13.3, tertiary aortic open procedure 7.4%, 4.0–13.2) were not negligible. Conclusions: In the secondary open aortic procedure population, type B dissection was both the most common pathology and the one associated with the lowest early mortality, whereas aortic infection and extra‐anatomical bypass were associated with the most ominous prognosis.